CONCEPTS OF OPERATIONS FOR A US DOSIMETRY AND BIODOSIMETRY NETWORK. Issue 1 (6th February 2019) - Dainiak, Nicholas; Albanese, Joseph; Kaushik, Meetu; Balajee, Adayabalam S; Romanyukha, Alexander; Sharp, Thad J; Blakely, William F
ABSTRACT: The USA must be prepared to provide a prompt, coordinated and integrated response for radiation dose and injury assessment for suspected radiation exposure, whether it involves isolated cases or mass casualties. Dose estimation for radiation accidents typically necessitates a multiple parameter diagnostics approach that includes clinical, biological and physical dosimetry to provide an early-phase radiation dose. A US Individual Dosimetry and Biodosimetry Network (US-IDBN) will increase surge capacity for civilian and military populations in a large-scale incident. The network's goal is to leverage available resources and provide an integrated biodosimetry capability, using multiple parameter diagnostics. Initial operations will be to expand an existing functional integration of two cytogenetic biodosimetry laboratories by developing Standard Operating Procedures, cross-training laboratorians, developing common calibration curves, supporting inter-comparison exercises and obtaining certification to process clinical samples. Integration with certified commercial laboratories will increase surge capacity to meet the needs of a mass-casualty incident.